Conditional analysis of free will and consequence argument - M. A. Sekatskaya (Омский научный вестник: Серия "Общество. История. Современность")
The conditional analysis of the meaning of the phrase “free will” is a classical compatibilist strategy, first introduced by David Hume and still widely used by compatibilists. The consequence argument is an influential argument against compatibilism. If the consequence argument is sound, then physical determinism is incompatible with alternative possibilities for any agent. In this article, I consider the relationship between the consequence argument and classical compatibilism. I demonstrate that the consequence argument uses premises that should be rejected by proponents of the counterfactual conditional analysis of free will